2018
DOI: 10.1038/s41598-018-34412-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq transcriptomic profiling of primary murine microglia treated with LPS or LPS + IFNγ

Abstract: Microglia, the main resident immune cells in the CNS, are thought to participate in the pathogenesis of various neurological disorders. LPS and LPS + IFNγ are stimuli that are widely used to activate microglia. However, the transcriptomic profiles of microglia treated with LPS and LPS + IFNγ have not been properly compared. Here, we treated murine primary microglial cultures with LPS or LPS + IFNγ for 6 hours and then performed RNA-Sequencing. Gene expression patterns induced by the treatments were obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 75 publications
3
39
0
Order By: Relevance
“…We investigated further LPS-IFN-γ effect since it simulates in vivo damage-associated molecular patterns acting on Toll-like receptors and IFN-γ produced by CNS cells (Pulido-Salgado et al., 2018). APPswe iMGLs produced less TNF-α and MCP1 in response to LPS-IFN-γ compared with control iMGLs (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated further LPS-IFN-γ effect since it simulates in vivo damage-associated molecular patterns acting on Toll-like receptors and IFN-γ produced by CNS cells (Pulido-Salgado et al., 2018). APPswe iMGLs produced less TNF-α and MCP1 in response to LPS-IFN-γ compared with control iMGLs (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that reactive microglia and astrocytosis (gliosis) play significant roles in neuroinflammation [2], and the activation of these glial cells releases several inflammatory cytokines, which eventually leads to neuroinflammation-mediated neurodegeneration [3]. Lipopolysaccharide (LPS) is a membrane component of Gram-negative bacteria [4], which activates the immune system and leads to behavioral and memory impairments, oxygen species (ROS) generation, lipid per oxidation (LPO), and consequently oxidative brain damage [5,6]. Previous studies suggest that dormant, non-growing bacteria are a crucial contributing factor in AD, and these bacteria release several inflammatory components such as LPS [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…It was well recognized that a series of genes involved in LPS-induced in ammation [18][19][20]. In this study, the DE mRNAs functional enrichment results showed that these genes were related to some biological processes, including in ammatory response, immune response, cytokine activity, chemokine activity, cytokine-cytokine receptor interaction, TNF signal pathway, NF-κB signal pathway, JAK-STAT signal pathway, NOD-like receptor signal pathway and TLR signal pathway, which were closely associated with LPS-induced in ammation [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%